Low-power total reflection X-ray fluorescence spectrometer using diffractometer guide rail. Issue 1 (15th October 2014) - Liu, Ying; Imashuku, Susumu; Kawai, Jun
Abstract : An X-ray diffractometer (XRD) was modified to a low-power total reflection X-ray fluorescence (TXRF) spectrometer. This was realized by reducing the XRD tube power (3 kW) down to 10 W by a Spellman power supply. The present spectrometer consisted of a waveguide slit, Si-PIN detector, a goniometer and two Z -axis stages that were set on a diffractometer guide rail. This unit was easy in assembly. The first measurements with this spectrometer were presented. The minimum detection limit for Cr was estimated to be a few nanograms or at the level of 10 13 atoms cm −2 .